FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI SUSU SAPI PERAH KELOMPOK TANI TERNAK SAPI PERAH (KTTSP) KANIA, KABUPATEN BOGOR - Adam Adinegoro; Edmon Daris; Zulmanery Z (Syarif Hidayatullah State Islamic University Jakarta, 2017)
The purpose of this study are: (1) to identify and to analyze the factors that influence milk production of dairy cattles, and (2) to determine the elasticity of milk production. This research was conducted at the Dairy cattle group KANIA, Bogor. Data were obtained from interviews and questionnaires with cattle ranchers. Multiple linear regression models and elasticity calculations were employed to analyze the data with the Excel 2007 and software for Statistical Product and Service Solution (SPSS) version 16. Results of the analysis revealed that the factors affecting milk production is labor, forages, and feed concentrates. The result of the calculation of the elasticity indicated that all production variables are elastic variables.